Data Quality: Provenance, Processing and Preservation. (17th February 2022) - Madhavan, Naveen
Abstract: Concerns about service quality extend beyond IT systems to actual data, writes Naveen Madhavan MBCS, Senior Product Specialist (Pathology) at Digital Health and Care Wales. Yet, the value of this data primarily resides in the insight it promises within a relevant context.